Starting from the needs: what are the appropriate sources to co-create innovative solutions for persons with disabilities? - Mensah-Gourmel, Johanne; Bourgain, Maxime; Kandalaft, Christèle; Chatelin, Alain; Tissier, Odile; Letellier, Guy; Gorter, Jan Willem; Brochard, Sylvain; Pons, Christelle (Disability & Rehabilitation: Assistive Technology, 2024)
Technical solutions could facilitate activities and participation in individuals with disabilities. For the development of solutions, hackathons are a method of interdisciplinary collaboration. For hackathon, the definition of pain points that require solutions is crucial. We aimed to determine engineers' preferences and expectations regarding pain point qualities. We used a collaborative approach involving individuals with disability, families, and healthcare professionals to determine pain points for use by engineering students during a disability Hackathon. A pain point bank was built using 3 upstream sources: a survey (350 responses, 20 pain points selected), interviews (8 children, 13 pain points), and a multidisciplinary workshop based on design thinking methods (45 people, 32 pain points). A fourth source was 20 adults with disabilities present during the Hackathon. Engineering students rated pain point qualities from each source in a questionnaire that included closed questions relating to predefined criteria: achievability, specificity, relevance and attractiveness and open questions to collect non-predefined quality criteria. Pain points from the workshop were most frequently used (48%); followed by on-site discussions with mentors (43%), the survey (38%), and interviews (31%). On-site discussions received the highest quality ratings followed by the workshop, survey, and interviews. Three quality criteria emerged from the responses to open questions: "representative", "empathy", and "real-need". To be actionable by engineers, pain points must relate to real needs, be achievable, specific, relevant and attractive but also representative and arouse empathy. We devised a checklist of qualities along with a toolbox of methods to achieve each. The first step of the development of technical solutions for children and individuals with disabilities is the identification of their needs and their adequate formulation to be submitted to technical solutions providers. Daily life needs of individuals with disability were gathered for an engineering hackathon and proposed as pain points to 400 engineering students. To facilitate the development of solutions by engineers, pain points must relate to real needs, be specific, relevant, achievable and attractive; be representative and arouse empathy; a toolbox of needs collection methods is proposed to achieve each of those qualities. Discussions with individuals with disability and health professionals should be provided.